Morphine Induces Desensitization of Insulin Receptor Signaling - Li, Yu (American Society for Microbiology, 2003)
Morphine analgesia is mediated principally by the μ-opioid receptor (MOR). Since morphine and other opiates have been shown to influence glucose homeostasis, we investigated the hypothesis of direct cross talk between the MOR and the insulin receptor (IR) signaling cascades. We show that prolonged morphine exposure of cell lines expressing endogenous or transfected MOR, IR, and the insulin substrate 1 (IRS-1) protein specifically desensitizes IR signaling to Akt and ERK cascades. Morphine caused serine phosphorylation of the IR and impaired the formation of the signaling complex among the IR, Shc, and Grb2. Morphine also resulted in IRS-1 phosphorylation at serine 612 and reduced tyrosine phosphorylation at the YMXM p85-binding motifs, weakening the association of the IRS-1/p85 phosphatidylinositol 3-kinase complex. However, the IRS-1/Grb2 complex was unaffected by chronic morphine treatment. These results suggest that morphine attenuates IR signaling to Akt by disrupting the IRS-1-p85 interaction but inhibits signaling to ERK by disruption of the complex among the IR, Shc, and Grb2. Finally, we show that systemic morphine induced IRS-1 phosphorylation at Ser612 in the hypothalamus and hippocampus of wild type, but not MOR knockout, mice. Our results demonstrate that opiates can inhibit insulin signaling through direct cross talk between the downstream signaling pathways of the MOR and the IR.